Association between MTHFR C677T polymorphism and abdominal aortic aneurysm risk: A comprehensive meta-analysis with 10, 123 participants involved. Issue 36 (September 2016) - Liu, Jie; Jia, Xin; Li, Haifeng; Jia, Senhao; Zhang, Minhong; Xu, Yongle; Du, Xin; Zhang, Nianrong; Lu, Weihang; Guo, Wei
Abstract: Background: Abdominal aortic aneurysm (AAA) is a life-threatening condition. A number of studies reported the association between methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism and AAA risk, but substantial controversial findings were observed and the strength of the association remains unclear. Objective: The aim of this study was to investigate the aforementioned association in the overall population and different subgroups. Methods: PUBMED and EMBASE databases were searched until March 2016 to identify eligible studies, restricted to humans and articles published in English. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were used to evaluate the susceptibility to AAA. Subgroup meta-analyses were conducted on features of the population, such as ethnicity, sex of the participants, and study design (source of control). Results: Twelve case–control studies on MTHFR C677T polymorphism and AAA risk, including 3555 cases and 6568 case-free controls were identified. The results revealed no significant association between the MTHFR C677T polymorphism and AAA risk in the overall population and within Caucasian or Asian subpopulations in all 5 genetic models. Further subgroup meta-analysis indicated that significantly increased risks were observed among cases with a mean age <70 years (OR = 1.73, 95% CI = 1.10–2.12, P = 0.02), cases with prevalence of smoking <60% (OR = 1.39, 95% CI = 1.02–1.90, P = 0.04), and cases with aneurysm diameter ≥55 mm (OR = 1.55, 95% CI = 1.07–2.24, P = 0.02) in the dominant genetic model. No publication bias was detected in the present study. Conclusion: In conclusion, our comprehensive meta-analysis suggests that the MTHFR C677T polymorphism may play an important role in AAA susceptibility, especially in younger, non-smoking, larger AAA-diameter subgroups of patients